What can stimulated emission do for bioimaging?. (21st May 2013) - Wei, Lu; Min, Wei
Abstract : Advances in bioimaging have revolutionized our ability to study life phenomena at a microscopic scale. In particular, the stimulated emission process, a universal mechanism that competes with spontaneous emission, has emerged as a powerful driving force for advancing light microscopy. The present review summarizes and compares three related techniques that each measure a different physical quantity involved in the stimulated emission process in order to tackle various challenges in light microscopy. Stimulated emission depletion microscopy, which detects the residual fluorescence after quenching, can break the diffraction‐limited resolution barrier in fluorescence microscopy. Stimulated emission microscopy is capable of imaging nonfluorescent but absorbing chromophores by detecting the intensity gain of the stimulated emission beam. Very recently, stimulated emission reduced fluorescence microscopy has been proposed, in which the reduced fluorescence due to focal stimulation is measured to extend the fundamental imaging‐depth limit of two‐photon microscopy. Thus, through ingenious spectroscopy design in distinct microscopy contexts, stimulated emission has opened up several new territories for bioimaging, allowing examination of biological structures that are ever smaller, darker, and deeper.